2017
DOI: 10.3847/2041-8213/aa8bff
|View full text |Cite
|
Sign up to set email alerts
|

Three Statistically Validated K2 Transiting Warm Jupiter Exoplanets Confirmed as Low-mass Stars

Abstract: We have identified three K2 transiting star-planet systems, K2-51 (EPIC 202900527), K2-67 (EPIC 206155547), and K2-76 (EPIC 206432863), as stellar binaries with low-mass stellar secondaries. The three systems were statistically validated as transiting planets, and through measuring their orbits by radial velocity (RV) monitoring we have derived the companion masses to be . Therefore, they are not planets but small stars, part of the small sample of low-mass stars with measured radius and mass. The three system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…It is worth noting that six validated planets have recently been shown to be false positives by follow-up observations and analysis (Cabrera et al 2017;Shporer et al 2017). We briefly examine whether these instances are a cause for concern in our own results.…”
Section: Criteria For Planet Validationmentioning
confidence: 85%
See 1 more Smart Citation
“…It is worth noting that six validated planets have recently been shown to be false positives by follow-up observations and analysis (Cabrera et al 2017;Shporer et al 2017). We briefly examine whether these instances are a cause for concern in our own results.…”
Section: Criteria For Planet Validationmentioning
confidence: 85%
“…The first two false positives would have failed the variable-sized mask test we apply via our diagnostic plots, while the secondary eclipse from the third false positive would have been caught through a combination of our data reduction process and the model-shift uniqueness test we apply . As for Shporer et al (2017), the vespa fit to the available photometry for each false positive was very poor and all three of the false positives were reported to be very large "planets." We addressed these concerns in two ways.…”
Section: Criteria For Planet Validationmentioning
confidence: 99%
“…We used the spectroscopic parameters from MacDonald et al (2016) and Petigura et al (2017) as inputs for Kepler-80 and Kepler-90, respectively, and we included near-infrared photometry from the 2MASS survey (Skrutskie et al 2006). Recently, it has been shown that systematic photometric uncertainties and/or offsets between photometric data sets can cause vespa to misclassify planet candidates (Shporer et al 2017;Mayo et al 2017, in preparation), so we avoided this issue by only including the high-quality 2MASS photometry.…”
Section: False-positive Probability Calculationsmentioning
confidence: 99%
“…First, the discovery of WASP-33b (Collier Cameron et al 2010) demonstrated that a combination of Doppler tomography and a robust upper limit on the companion mass from RV can confirm a transiting planet. Second, the use of statistical tools by the Kepler mission also relaxed the perception that RV confirmation was needed to validate a planet (Torres et al 2011;Morton 2012;Lissauer et al 2014; although see Shporer et al 2017, for an example of the pitfalls of statistical validation). These changes, together with the somewhat fortuitous and accidental discovery of KELT-1b , led the KELT Collaboration to pursue planets around more massive and hotter stars.…”
Section: Introductionmentioning
confidence: 99%